2*x=3 y2-2*x*y+4*x-1=0

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
2*x = 3
$$2 x = 3$$
y2 - 2*x*y + 4*x - 1 = 0
$$4 x + - 2 x y + y_{2} - 1 = 0$$
Быстрый ответ
[LaTeX]
$$x_{1} = \frac{3}{2}$$
=
$$\frac{3}{2}$$
=
1.5

$$y_{1} = \frac{1}{3} \left(y_{2} + 5\right)$$
=
$$\frac{y_{2}}{3} + \frac{5}{3}$$
=
1.66666666666667 + 0.333333333333333*y2